The Forkhead Box M1 protein regulates BRIP1 expression and DNA damage repair in epirubicin treatment - Monteiro, Lara J. (2012)
FOXM1 is implicated in genotoxic drug resistance but its role and mechanism of action remain unclear. Here, we establish that γH2AX foci, indicative of DNA double strand breaks, accumulate in a time-dependent manner in the drug sensitive MCF-7 cells but not in the resistant counterparts in response to epirubicin. We find that FOXM1 expression is associated with epirubicin sensitivity and double strand break (DSB) repair. Ectopic expression of FOXM1 can increase cell viability and abrogate DSBs sustained by MCF-7 cells following epirubicin, owing to an enhancement in repair efficiency. Conversely, alkaline comet and γH2AX foci formation assays show that Foxm1-null cells are hypersensitive to DNA damage, epirubicin and γ-irradiation. Furthermore, we find that FOXM1 is required for DNA repair by homologous recombination (HR) but not non-homologous end joining (NHEJ), using HeLa cell lines habouring an integrated direct repeat green fluorescent protein (DR-GFP) reporter for DSB repair. We also identify BRIP1 as a direct transcription target of FOXM1 by promoter analysis and chromatin-immunoprecipitation assay. In agreement, depletion of FOXM1 expression by siRNA down-regulates BRIP1 expression at the protein and mRNA levels in MCF-7 and the epirubicin resistant MCF-7 Epi(R) cells. Remarkably, the requirement for FOXM1 for DSB repair can be circumvented by reintroduction of BRIP1, suggesting that BRIP1 is an important target of FOXM1 in DSB repair. Indeed, like FOXM1, BRIP1 is needed for HR. These data suggest that FOXM1 regulates BRIP1 expression to modulate epirubicin-induced DNA damage repair and drug resistance.